HETEROGENEOUS CATALYSIS USING BENTONITE-SUPPORTED Fe-Co-Ni TRIMETALLIC NANOPARTICLES - ADERIBIGBE FATAI ALADE; ADEWOYE TUNMISE LATIFAT; MUSTAPHA SHERIF ISHOLA; MOHAMMED ISHAQ ALHASSAN; SAKA HARVIS BAMIDELE; AJALA ELIJAH OLAWALE; OLUWASEYI SOILE SAMUEL (Journal of Engineering Studies and Research)
Herein, the synthesis and characterization of a bentonite-supported Fe-Co-Ni trimetallic nanocatalyst applied in transesterification reaction was reported. The synthesized heterogeneous catalyst was used to investigate the production of biodiesel by varying the reaction parameters using Box-Behnken design response surface methodology (RSM-BBD). An optimum biodiesel yield of 95.2 % was obtained at methanol to oil ratio of 10:1, reaction time of 2 hours, reaction temperature of 55  and catalyst concentration of 5 % (w/w of the oil). The biodiesel produced was later analysed using GC-MS analysis and the results shows a fatty acid methyl esters (FAME) profile that confirms the presence of biodiesel.